Teachers’ Efficacy to Teach Students with Mathematics Learning Difficulties - Soo May Yoong; Fu Sai Hoe (Journal of Mathematics Instruction, Social Research and Opinion, 2022)
This study explores teachers’ perceptions of their efficacy in teaching students with mathematics learning difficulties, also known as dyscalculia. This study employed a quantitative survey method. Random cluster sampling was used to select 384 mathematics teachers in the survey. Teaching Students with Mathematics Learning Difficulties Scale has been adapted with permission from Dawson & Scott (2013). Inferential statistics of independent t-test, analysis of variance, and Kruskal Wallis H-test were used to analyze the data. The results showed that teachers have high efficacy in teaching students with mathematics learning difficulties. There is no significant difference in teachers’ effectiveness in teaching students with mathematics learning difficulties based on age groups and years of experience. However, the findings show a significant difference in teachers’ effectiveness based on different academic qualifications. This study implies that the awareness of dyscalculia among mathematics teachers has increased. Future researchers are suggested to design and develop more interventions and instruments to improve the basic mathematical skills among students with mathematics learning difficulties.